Histopathology and contaminant concentrations in fish from Kuwait's marine environment. Issue 2 (30th November 2015) - Al-Zaidan, A.S.; Al-Sarawi, H.A.; Massoud, M.S.; Al-Enezi, M.; Smith, A.J.; Bignell, J.P.; Green, M.J.; Askem, C.; Bolam, T.P.C.; Barber, J.L.; Bersuder, P.; Lyons, B.P.
Abstract: Kuwait has witnessed major socioeconomic and industrial development in recent decades. Consequently, a variety of contaminants related to these activities have been discharged directly into the marine environment. This paper describes the application of a histopathology baseline survey in two potential sentinel species, the Giant sea catfish ( Arius thalassinus ) and the Fourlined terapon ( Pelates quadrilineatus ) to assess the health of biota inhabiting Kuwait's marine environment. Histological analysis revealed several lesion types in both species, although the prevalence was generally considered low with no discernible differences between sampling locations. The analysis of contaminant burdens (metals, PCBs, PBDEs, HBCDD) in A. thalassinus, along with the analysis of bile for PAH metabolites in both species, indicated that levels of contaminant exposure was low. Overall the data show that both species appear to be susceptible to pathologies associated with environmental contaminants and therefore suitable for further investigation as sentinel organisms for biological effects monitoring. Highlights: Histopathological survey of two species of fish caught in Kuwait marine waters. Levels of contaminants relatively low and not toxicologically significant. Low prevalence of pathologies related to chemical exposure observed.